Criminal Law Aspects of Socially Adequate Customs and Traditions - Stajnko, Jan (65 pravne znanosti v Mariboru, 2026)
Social customs are based on the repetition of a certain type of behaviour and represent a spontaneous "agreement" within societal practice. However, behaviour in line with established social patterns may be at odds with criminal law provisions. This chapter addresses the question of how to deal with such cases, where a person acts in harmony with traditional practices, yet, at least in a formal sense, commits a criminal offence. It delves into traditions that have recently garnered public outrage – from hazing of first-year students to carnival-mascot harassment of women in the village of Markovci. The author then shows that some examples of social customs could be tackled via the concept of social adequacy, which has been developed in German criminal law doctrine.